2023
DOI: 10.3390/endocrines4010003
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated with Increased F2-Isoprostanes and IL-6 in Black Women

Abstract: Obesity affects over 40% of the adult population and is a major risk factor for morbidity and mortality due to cardiovascular disease. Black women have one of the highest prevalences of obesity, insulin resistance, hypertension, and cardiovascular events in the US. We previously found that free radical-mediated lipid peroxidation contributes to IL-6 production in dendritic cells leading to inflammation and hypertension. Thus, we hypothesized that F2-isoprostanes (F2-IsoPs), products and biomarkers of endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Obesity is related to high IR and type 2 diabetes 21 ; many studies show that remodeling adipose tissue in obese individuals triggers the release of pro-inflammatory cytokines and chemokines, which can lead to systemic inflammation and IR. 22,23,24,25 The average ± SD of HOMA-IR in the obese diabetics was higher than in obese non-diabetics with 3.81 ± 1.12 and 1.41 ± 1.13, respectively; this relationship is surprising and confirms that obesity is a risk factor for non-diabetic obesity to become diabetic. 26 In the overweight or adiposity, IR initially triggers compensatory mechanisms, resulting in insulin hypersecretion that temporarily keeps blood sugar levels under control.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Obesity is related to high IR and type 2 diabetes 21 ; many studies show that remodeling adipose tissue in obese individuals triggers the release of pro-inflammatory cytokines and chemokines, which can lead to systemic inflammation and IR. 22,23,24,25 The average ± SD of HOMA-IR in the obese diabetics was higher than in obese non-diabetics with 3.81 ± 1.12 and 1.41 ± 1.13, respectively; this relationship is surprising and confirms that obesity is a risk factor for non-diabetic obesity to become diabetic. 26 In the overweight or adiposity, IR initially triggers compensatory mechanisms, resulting in insulin hypersecretion that temporarily keeps blood sugar levels under control.…”
Section: Discussionmentioning
confidence: 88%
“…So, the data showed a highly significant difference in the levels of HOMA‐IR in both groups. Obesity is related to high IR and type 2 diabetes 21 ; many studies show that remodeling adipose tissue in obese individuals triggers the release of pro‐inflammatory cytokines and chemokines, which can lead to systemic inflammation and IR 22,23,24,25 . The average ± SD of HOMA‐IR in the obese diabetics was higher than in obese non‐diabetics with 3.81 ± 1.12 and 1.41 ± 1.13, respectively; this relationship is surprising and confirms that obesity is a risk factor for non‐diabetic obesity to become diabetic 26 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has shown that African American individuals have a greater oxidative stress response to lipid infusion at doses of 0.8 mL/m 2 /min with heparin (200 U/hrs for 4 hrs) than in Whites (Lopes et al., 2003), which is confirmed by plasma levels of the oxidative stress biomarker F2‐isoprostane (Parsa et al., 2022; Saleem et al., 2023). However, a reliable protocol to measure dynamic changes in oxidative stress responses in human endothelial cells has yet to be developed.…”
Section: Introductionmentioning
confidence: 83%
“…7,9,11 This promotes oxidation of arachidonic acid and formation of IsoLGs (isolevuglandins) through the isoprostane endoperoxide pathway. 11,49 The IsoLGs covalently bind to lysines on proteins and form lipid-protein adducts that permanently alter protein structure and function. These altered proteins are recognized as foreign and induce an autoimmune-like state in hypertension.…”
Section: Reactive Oxygen Species and Isolevuglandins In Inflammation ...mentioning
confidence: 99%